Peran Edukasi Gizi terhadap Pengetahuan Gizi Seimbang dan Aktivitas Fisik pada Siswa SMA/Sederajat di Banten - Mukhlidah Hanun Siregar; Ratu Diah Koerniawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
Obesity is one of the most common nutritional problems in adolescents. The report from Basic Health Survey (Riskesdas) showed an increase the prevalence of obesity in adolescents, as 7.5% (2013) and 9.5% (2018). Obesity is also a risk factor for degenerative diseases. This activity was held to provide information on balanced nutrition guidelines and physical activity to prevent obesity during the Covid-19 pandemic. Education on balanced nutrition guidelines and physical activity was held by Zoom meeting. The targets of this activity were students in senior high school in Banten. The results showed that there was an increase of average knowledge score after nutrition education, from 7.48 to 14.09, and there was a significant difference between knowledge scores before and after the nutrition education (p value = 0.000). This results shows that the online method using zoom meeting is one of choice for the implementation of nutrition education in the community during the Covid-19 pandemic.